2013
DOI: 10.4314/mejs.v5i1.85333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sesame cake supplementation on feed intake, body weight gain, feed conversion efficiency and carcass parameters in the ration of sheep fed on wheat bran and teff (<i>Eragrostis teff</i>) straw

Abstract: Twenty-five yearling growing intact sheep were arranged in randomized complete block design (RCBD) with five treatments and five replications. The experimental animals were supplied teff straw as basal ration. Different levels of sesame cake were supplemented in various treatment groups i.e. T 1 (150 gm wheat bran, 0 gm sesame seed cake DM/day) being control group, T 2 (150 gm wheat bran, 150 gm sesame seed cake DM/day), T 3 (150 gm wheat bran, 200 gm sesame seed cake DM/day), T 4 (150 gm wheat bran, 250 gm se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
9
10
0
Order By: Relevance
“…This was related to lower costs of rations containing sesame oil cake (Abo Omar 2002). On the other hand, Fitwi and Tadesse (2013) showed that using 300 g DM of sesame seed cake was potentially more feasible and economically beneficial for growing sheep. Also, Mahmoud and Bendary (2014) noted that the use of sesame seed meal reduced feed cost, and therefore it can be used to improve total revenue, net revenue, economic efficiency, and relative economic efficiency in ration on performance of growing lambs and calves.…”
Section: Discussionmentioning
confidence: 99%
“…This was related to lower costs of rations containing sesame oil cake (Abo Omar 2002). On the other hand, Fitwi and Tadesse (2013) showed that using 300 g DM of sesame seed cake was potentially more feasible and economically beneficial for growing sheep. Also, Mahmoud and Bendary (2014) noted that the use of sesame seed meal reduced feed cost, and therefore it can be used to improve total revenue, net revenue, economic efficiency, and relative economic efficiency in ration on performance of growing lambs and calves.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis on the milk showed that in winter, when the pasture is unavailable, the amount of healthy fatty acid increased [37]. Satisfactory carcass yield and feedlot performance (body weight gain, feed conversion efficiency) also were observed with the addition up to 20% (300g) of groundnut and sesame oilcakes [177,178]. Sesame meal also improved intake, digestibility and rumen condition in lambs without changing performance and carcass composition [179].…”
Section: Animal Feedstuffmentioning
confidence: 96%
“…The most common application of sesame residues is compost with carbon compounds to fertilise the land, feedstuff for poultry, swine, and fish. Sesame cake as supplementation on feed can increase body weight gain and enhance carcass parameters of sheep (Fitwi and Tadesse, 2013), increase daily gain and feed conversion efficiency of Awassi lambs (Omar, 2002), and increase growth and feed conversion ratio of carp (Mazid et al, 1997). Nevertheless, when it is used as poultry feed, there is a growth restriction when feed ingredient is substituted with sesame residues by 30% (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%